A Novel Three-Dimensional Chiral Cadmium-Tartrate Compound: Hydrothermal Synthesis and Crystal Structures - Feng, Guo-Dong; Jiang, Luan (Asian Journal of Chemistry, 2013)
One novel cadmium-tartrate compound exhibiting three-dimensional chiral structure, namely [Cd3(TTA)3(H2O)](H2O)2n (1) (H2TTA = tartaric acid), was obtained by the reactions of the cadmium salts with corresponding H2TTA under hydrothermal conditions and characterized by X-ray single-crystal diffraction and elemental analysis. The crystal belongs to the orthorhombic system, space group P212121 with a = 0.63507(8) nm, b = 1.7116(2) nm, c = 1.8492(2) nm, a = b = g = 90º, V = 2.0101(4) nm3, Dc = 2.717 g cm-3, Z = 4, F(000) = 1556, Goof = 1.033, R1 = 0.0326, wR2 = 0.0703. The compound 1 shows an interesting three-dimensional network with left helical chains. CCDC: 837585.